2009
DOI: 10.1098/rsbl.2008.0722
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea mystery solved: astonishing larval transformations and extreme sexual dimorphism unite three fish families

Abstract: The oceanic bathypelagic realm (1000–4000 m) is a nutrient-poor habitat. Most fishes living there have pelagic larvae using the rich waters of the upper 200 m. Morphological and behavioural specializations necessary to occupy such contrasting environments have resulted in remarkable developmental changes and life-history strategies. We resolve a long-standing biological and taxonomic conundrum by documenting the most extreme example of ontogenetic metamorphoses and sexual dimorphism in vertebrates. Based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 9 publications
0
58
0
Order By: Relevance
“…In extreme cases, different life-history stages or sexes can wrongly be attributed to different taxa (e.g. Johnson et al 2009), confounding estimates of connectivity. When the different sexes or stages inhabit different environments such as different depths, estimating dispersal from a single life stage or sex can bias interpretation of connectivity patterns but also taxonomic interpretations (Box 1).…”
Section: Methodological Considerations and Guidelines For Connectivitmentioning
confidence: 99%
See 1 more Smart Citation
“…In extreme cases, different life-history stages or sexes can wrongly be attributed to different taxa (e.g. Johnson et al 2009), confounding estimates of connectivity. When the different sexes or stages inhabit different environments such as different depths, estimating dispersal from a single life stage or sex can bias interpretation of connectivity patterns but also taxonomic interpretations (Box 1).…”
Section: Methodological Considerations and Guidelines For Connectivitmentioning
confidence: 99%
“…First, the state of the art of taxonomy may be so preliminary that different life stages of a single organism might have been erroneously classified as different species or even families (e.g. Johnson et al 2009). Second, the evidence that two evolutionary lineages are engaged in definitive divergence may not be easy to evaluate when the split between the emergent lineages is recent (the 'grey zone' of de Queiroz 1998).…”
Section: Theoretical Framework For Delimiting Species: a Primermentioning
confidence: 99%
“…Not until 1991 did R. K. Johnson and E. Bertelsen publish the definitive morphological evidence documenting the remarkable ontogenetic changes that remodel the 'rosaura' larva into the highly specialized giganturid adult form. In 2009, G. D. Johnson and coworkers (Johnson et al 2009) documented the ''most extreme example of ontogenetic metamorphoses and sexual dimorphism in vertebrates'' when they showed that fishes then assigned to three families with very different morphologies-Mirapinnidae, Megalomycteridae and Cetomimidae-were larvae, males and females, respectively, of one family. The Mirapinnidae, described as a new order in 1956 (Bertelsen and Marshall 1956), lacks scales and lateral lines, but has a large mouth with almost vertically oriented jaws and, in most individuals, a long ribbon-like streamer formed from the skin of the caudal fin.…”
Section: Ontogeny and Systematicsmentioning
confidence: 99%
“…Sexual dimorphism in fishes most commonly involves external features that play a role during reproductive behaviour and that range from variably sized fins [14,15], teeth and/or jaws [16,17] in males to extreme differences in body size [18] and/or shape [19] between the sexes. Sexual dimorphism of internal organs other than the gonads is rare, not only among fishes, but also in other groups of vertebrates, and is limited to a few examples, including (but not restricted to) the sexually dimorphic kidney of sticklebacks [20], salamanders [21] and squamates [22] and the larynx in vocal tetrapods [23].…”
Section: Resultsmentioning
confidence: 99%